Characterization and referral patterns of ST-elevation myocardial infarction patients admitted to chest pain units rather than directly to catherization laboratories: data from the German Chest Pain Unit Registry - Schmidt, Frank Patrick; Hochadel, Matthias; Giannitsis, Evangelos; Senges, Jochen (International journal of cardiology, 2017)
Background: Direct transfer to the catheterization laboratory for primary percutaneous coronary intervention (PCI) is standard of care for patients with ST-segment elevation myocardial infarction (STEMI). Nevertheless, a significant number of STEMI-patients are initially treated in chest pain units (CPUs) of admitting hospitals. Thus, it is important to characterize these patients and to define why an important deviation from recommended clinical pathways occurs and in particular to quantify the impact of deviation on critical time intervals. Methods and results: 1679 STEMI patients admitted to a CPU in the period from 2010 to 2015 were enrolled in the German CPU registry (8.5% of 19,666). 55.9% of the patients were delivered by an emergency medical system (EMS), 16.1% transferred from other hospitals and 15.2% referred by a general practitioner (GP). 12.7% were self-referrals. 55% did not get a pre-hospital ECG. Compared to the EMS, referral by GPs markedly delayed critical time intervals while a pre-hospital ECG demonstrating ST-segment elevation reduced door-to-balloon time. When compared to STEMI patients (n=21,674) enrolled in the ALKK-registry, CPU-STEMI patients had a lower risk profile, their treatment in the CPU was guideline-conform and in-hospital mortality was low (1.5%). Conclusions: CPU-STEMI patients represent a numerically significant group because a pre-hospital ECG was not documented. Treatment in the CPU is guideline-conform and the intra-hospital mortality is low. The lack of a pre-hospital ECG and admission via the GP substantially delay critical time intervals suggesting that in patients with symptoms suggestive an ACS, the EMS should be contacted and not the GP.
Gesehen am 23.05.2018